1969
DOI: 10.1111/j.2044-8279.1969.tb02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety About School Among First‐year Grammar School Pupils, and Its Relation to Occupational Class and Co‐education

Abstract: A revised Boxall School Anxiety Test was administered to 1,120 first-year grammar school pupils in 42 schools in South Wales and the West Riding. After separating these into pupils from mixed, boys' and girls' schools, scores were seen to be consistently related to occupational class, the most anxious pupils being from the lower classes. Girls recorded a greater anxiety than boys. Pupils in single-sex schools had slightly higher scores than those in mixed schools, but both groups had only recently entered thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…The full SEI has test/retest reliabilities ranging from 0.88 over a 5-week period to 0.70 over a 3-year period (Coopersmith, 1967). In this study a shortened version of 25 questions was used which is reported to correlate a t 0.86 with the 58-item version (Argyle and Lee, 1972 (Boxall, 1961) modified by Dale (1969) …”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The full SEI has test/retest reliabilities ranging from 0.88 over a 5-week period to 0.70 over a 3-year period (Coopersmith, 1967). In this study a shortened version of 25 questions was used which is reported to correlate a t 0.86 with the 58-item version (Argyle and Lee, 1972 (Boxall, 1961) modified by Dale (1969) …”
Section: Variablesmentioning
confidence: 99%
“…The other variables selected as tests which are likely to be used in conjunction with ( I ) National Foundation for Educational Research Test D3 (2) Test DEl Mathematics (NFER, 1970) (3) Moray House Test 95 Verbal Reasoning (University of Edinburgh, 1977) (4) Academic Self-Image Scale (Barker Lunn, 1970) (5) The Boxall Test of School Anxiety (Boxall, 1961) modified by Dale (1969)…”
Section: Variablesmentioning
confidence: 99%
“…Άναφορικώς προς τήν άνευρεθίεϊσαν οχέσιν ιμεταξύ νευρωτικής συμπεριφοράς τών παιδίων καί κακής οικονομικής καταστάσεως τής οι κογενείας (πίναξ 19), δεν εχομεν να προσθέσωμεν τίποτε το νέον, διότι το σχετικον εύρημα συμφωνεί προς τήν γενικήν πεποίθησιν δτι ή δυστυ χία ευνοεί τάς ψυχικός διαταραχάς καί έπιοεβαιοί το λαϊκον ρητόν, «δπου φτώχεια καί γκρίνια». Ειδικώς ό Dale, 20 μελετών 1120 παιδία μέ -100σχολειοφοβίαν, εύρεν ότι τα περισσότερα άνηκον εις τας κοινωνικώς κατωτέρας τάξεις. Μεταξύ τών αλλων στοιχείων, τα παιδία μεταφέρουν εις το σχολικον περιβάλλον καί τάς εμπειρίας των έιπί τών μετά τών γονέων των διαπροσωπικών σχέσεων.…”
Section: _90 -unclassified